2016
DOI: 10.1002/ls.1366
|View full text |Cite
|
Sign up to set email alerts
|

Tribological properties of h-BN nanoparticles as lubricant additive on cylinder liner and piston ring

Abstract: Friction and wear behaviour of different concentrations of hex-boron nitride (h-BN) nanoparticles in engine oil of grade SAE 20W50 were studied at various loads. These tribological studies were conducted using a four-ball wear test machine and a pin-on-disc universal tribometer. Anti-wear properties of SAE 20W50 + h-BN were studied on the four-ball wear test machine as per ASTM D4172 standard. Friction and wear properties of SAE 20W50 + h-BN on piston ring and cylinder liner tribo-pair were studied using the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 20 publications
(25 reference statements)
1
60
0
Order By: Relevance
“…In this research study, it has been observed that the addition of nano-BN particles to SAE15W40 significantly improve the antifriction and antiwear properties of the SAE15W40 oil. Recently, tribological studies with the addition of different weight percentages of IF-MoS 2 in SAE20W40 and h-BN nanoparticles in SAE20W50 engine oil were conducted (Charoo and Wani (11), (12)). In these research studies, it has been observed that the addition of nanoparticles to engine oil significantly improved the tribological performance in internal combustion (IC) engine applications.…”
Section: Introductionmentioning
confidence: 99%
“…In this research study, it has been observed that the addition of nano-BN particles to SAE15W40 significantly improve the antifriction and antiwear properties of the SAE15W40 oil. Recently, tribological studies with the addition of different weight percentages of IF-MoS 2 in SAE20W40 and h-BN nanoparticles in SAE20W50 engine oil were conducted (Charoo and Wani (11), (12)). In these research studies, it has been observed that the addition of nanoparticles to engine oil significantly improved the tribological performance in internal combustion (IC) engine applications.…”
Section: Introductionmentioning
confidence: 99%
“…Since most of the existing lubricants have their performance limits, one of the important scientific tasks is to develop new lubricants that can achieve energy efficiency. Some new materials as potential lubricant additives have been experimentally evaluated through comparison analysis of their tribological behaviours . Layered zirconium phosphates are an important class of compounds owing to their potential applications in proton conductivity, ion exchange, adsorption, and catalysis .…”
Section: Introductionmentioning
confidence: 99%
“…Some new materials as potential lubricant additives have been experimentally evaluated through comparison analysis of their tribological behaviours. [3][4][5][6][7][8] Layered zirconium phosphates are an important class of compounds owing to their potential applications in proton conductivity, ion exchange, adsorption, and catalysis. [9][10][11][12][13] Recent study demonstrates that layered zirconium phosphates can be used as effective additives to promote lubrication in base oils and greases, [14][15][16][17] owing to relatively weak interlayer (ie, van der Waals) bonding, which is similar to that of MoS 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Although some work [15][16][17] has been reported using nanolubricants but no systematic representation of the gain in weight of the samples after the tribo test has been reported. The present work aimed at investigating the wear between two steel surfaces under micro and nano particles based lubricant and analysing the surfaces of the samples and also focussed on the weight gain after tribo tests with ZnO nano particle additions.…”
Section: Introductionmentioning
confidence: 99%